Understanding the current market enablers for Nepal's biomass cookstove industry. Issue 1 (2nd January 2022) - Robinson, Benjamin L.; Jewitt, Sarah; Clifford, Mike J.; Hewitt, Joseph
ABSTRACT: This paper applies the market map tool to the Nepalese biomass improved cookstove (ICS) sector highlighting existing weaknesses in government policy and biomass cookstove market chains to provide recommendations to better address the social, economic, and cultural needs of users. This addresses the problem of low adoption rates of biomass ICS in Nepal. Our research objectives set out to explore the effectiveness of market maps designed for East Africa's ICS sector (Stevens et al. [2019]. "Market Mapping for Improved Cookstoves: Barriers and Opportunities in East Africa." Development in Practice ) in Nepal, co-develop a revised market map for Nepal's biomass ICS sector, conduct a parallel process for institutional-scale biomass ICS and draw on the co-produced market map to inform policy and regulatory frameworks relating to biomass-fuelled ICS. The methodological approach involved reviewing cookstove-related policy documents and regulatory frameworks, undertaking 31 semi-structured interviews, analysing findings from an Institutional Top-Loading Down-Draft (TLUD) Natural Draft Gasifier Pilot study and co-developing the final market map in collaboration with key ICS stakeholders. The results indicate that although government policy actively promotes biomass ICS, this often results in cookstove "stacking" rather than the sustained and exclusive use of clean cooking solutions necessary to promote health benefits. Attention is also focused on the underdeveloped nature of the institutional cookstove market. Our conclusions highlight the usefulness of market maps with a monitoring and evaluation element for identifying barriers to clean cooking uptake and facilitating product improvement by integrating end-user feedback.